Rehabilitation of squares in the old cities: A case study of Al-Almaji Square in the city of Aleppo: إعادة تأهيل الساحات في المدن القديمة: دراسة حالة ساحة الألمجي في مدينة حلب - Hala Hussam Eddin Malandi, (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2022)
Squares are the soul of the city; because they play an effective role in the structure, life and identity of cities and the promotion of the urban environment in them, and are characterized by being enjoyable and can be accessed by everyone for free at any time. Each public square has its own spatial, historical, environmental, social and economic characteristics. Therefore, the identity and characteristics of the public urban squares must be developed and improved to match the place in which they are and with the change in the behavior of its users over time.The problem of the research is manifested in the lack of Al-Alamji Square in the old city of Aleppo to the spirit of the place within it, which is the traditional historical fabric in terms of its surrounding facades and in terms of its urban design, which affected its social, economic and cultural role. Therefore, the research aims at evaluating the Al-Alamji Square according to characteristics deduced from a theoretical documentary study of the bases for evaluating public squares internationally approved in this field and the stages of development of the squares historically, analyzing them and intersecting them together to conclude the most important factors that hinder public squares from performing their role, and on the other hand, the factors that support the squares to be socially, economically and culturally attractive.The research also reviews the experience of rehabilitating a new square in a historical area in Melbourne, taking advantage of the steps to address its design problems that affected its effectiveness, and then moves to the case study by evaluating it according to the theoretical and the deductive study. Suggestions, through illustrative sketches, to re-design Al-Alamji Square to accommodate different activities and modify its facades so as to harmonize with the traditional fabric of the area, increase the proportion of green spaces, determine the entrances to the square, and other suggestions, in order to improve its role as one of the important public spaces created in the old city of Aleppo.
Keywords: الساحات; المدن القديمة; تطوير; تقييم; خصائص مادية وغير مادية